2004
DOI: 10.1098/rspb.2004.2780
|View full text |Cite
|
Sign up to set email alerts
|

Neocortex size predicts deception rate in primates

Abstract: Human brain organization is built upon a more ancient adaptation, the large brain of simian primates: on average, monkeys and apes have brains twice as large as expected for mammals of their size, principally as a result of neocortical enlargement. Testing the adaptive benefit of this evolutionary specialization depends on finding an association between brain size and function in primates. However, most cognitive capacities have been assessed in only a restricted range of species under laboratory conditions. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(186 citation statements)
references
References 63 publications
(71 reference statements)
5
170
1
5
Order By: Relevance
“…Across primates, support for multiple, nonexclusive hypotheses for enlarged brain (particularly neocortex) size has been identified in comparative studies, emphasizing the roles of social complexity (e.g., group size) (28,29), ecological intelligence (e.g., dietary complexity) (30,31), technical intelligence (e.g., tool use and technical innovation) (21,25,32), and behavioral complexity (e.g., innovativeness, social learning, and tactical deception) (21,25,33). Further, several comparative studies have found that larger brained primates have slower life histories, including longer juvenile periods and overall lifespans (e.g., ref.…”
mentioning
confidence: 99%
“…Across primates, support for multiple, nonexclusive hypotheses for enlarged brain (particularly neocortex) size has been identified in comparative studies, emphasizing the roles of social complexity (e.g., group size) (28,29), ecological intelligence (e.g., dietary complexity) (30,31), technical intelligence (e.g., tool use and technical innovation) (21,25,32), and behavioral complexity (e.g., innovativeness, social learning, and tactical deception) (21,25,33). Further, several comparative studies have found that larger brained primates have slower life histories, including longer juvenile periods and overall lifespans (e.g., ref.…”
mentioning
confidence: 99%
“…Both EQ and SNQ, however, fail to take into consideration absolute size of brain structures, which has been shown to be related to some abilities, like deception in primates (Byrne and Corp, 2004). By definition, a large brain of large EQ would be expected to have much more excess brain mass than a small brain of similarly large EQ.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been noted that a variety of brain size variables in primates correlate positively with measures of social complexity, such as group size, deceptive behaviour, or strength of social bonds (Barton, 1996(Barton, , 1999Byrne & Corp, 2004;Dunbar, 1998;Dunbar & Shultz, 2007). This has been taken to suggest that large groups, and social complexity that emerges from them, have acted as a primary selection force favouring the evolution of increased brain size.…”
Section: Evolutionary Theories Of Primate Cognitionmentioning
confidence: 99%